Evolutionary Conservation of Hox Genes in Vertebrate Brain Development - G. Struemph Samantha; O. Henderson Jeffrey (Journal of Evolutionary Science, 2021)
Hox genes, their conserved derivatives, and the pathways responsible for their expression have been extensively studied in the fruit fly, Drosophila melanogaster;the experimentation done in the Drosophila model system has given developmental biologists tools to better understand the role and significance of Hox genes and their derivatives in anterior-posterior axis determination in the Drosophila embryo. Along with this, Drosophila research opened up the door to investigation on the conservation of Hox genes between vertebrates and invertebrates. Comparative embryology in mice, chickens, pufferfish, and zebrafish have shown conserved Hox gene expression patterns specifically along the anterior-posterior axis. Recently, comparative analysis performed on dorsal-ventral axis formation showed that patterning and segmentation of the spinal cord is influenced by the action of Hox genes as well. This review will briefly consider the evolution of the vertebrate brain and the evolution and conservation of Hox genes in regulating hindbrain patterning and spinal cord development.
Keywords: Hox genes